Miscible fluids mixing via alternating injection in a radial Hele-Shaw cell: experimental and numerical studies. (24th November 2022) - Chou, Chi-Chian; Kumar, Avdhesh; Lu, Po-Chun; Chen, Ching-Yao
Abstract: An alternating injection scheme is experimentally employed to study the mixing performance of miscible viscous fluids in a radial Hele-Shaw cell. The concept of the covered area is introduced to quantify the mixing efficiency and various numerical simulations are performed to support and verify the experimental results. It has been observed that the alternating injection can improve the mixing efficiency, depending on the prominence of the channeling interactions. The alternating injection can effectively improve the mixing efficiency under certain conditions, where weaker fingering interactions are dominated by diffusive mixing. However, the results under the high Péclet number conditions are inconsistent, i.e. the mixing efficiency is reduced due to the emergence of orderly viscous fingers prevailing random chaotic interactions. This phenomenon is similar to the channeling interaction in the heterogeneous permeability fields in which less viscous fluid flows through favorable paths due to the local pressure difference between two successively emerging fingers.